2019
DOI: 10.1371/journal.pbio.3000171
|View full text |Cite
|
Sign up to set email alerts
|

A genetic switch for worker nutrition-mediated traits in honeybees

Abstract: Highly social insects are characterized by caste dimorphism, with distinct size differences of reproductive organs between fertile queens and the more or less sterile workers. An abundance of nutrition or instruction via diet-specific compounds has been proposed as explanations for the nutrition-driven queen and worker polyphenism. Here, we further explored these models in the honeybee (Apis mellifera) using worker nutrition rearing and a novel mutational screening approach using the clustered regularly inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 63 publications
1
106
0
Order By: Relevance
“…Gene networks that regulate developmental plasticity may be a nexus of such regulatory changes that enable the evolution of social traits from ancient genes. Many of the genes underlying social behavior in insects respond to variable developmental conditions (e.g., diet, aggression, hormone levels) to produce adults with different behavioral traits (e.g., workers, queens) (32)(33)(34)(35)(36). Accordingly, the leading hypotheses proposed to explain how eusociality evolves from a solitary ancestor evoke developmental processes as a source of initial phenotypic variation for traits related to social behavior.…”
Section: Significancementioning
confidence: 99%
“…Gene networks that regulate developmental plasticity may be a nexus of such regulatory changes that enable the evolution of social traits from ancient genes. Many of the genes underlying social behavior in insects respond to variable developmental conditions (e.g., diet, aggression, hormone levels) to produce adults with different behavioral traits (e.g., workers, queens) (32)(33)(34)(35)(36). Accordingly, the leading hypotheses proposed to explain how eusociality evolves from a solitary ancestor evoke developmental processes as a source of initial phenotypic variation for traits related to social behavior.…”
Section: Significancementioning
confidence: 99%
“…For any researcher with average experience in beekeeping and microinjection, the number of eggs collected by FECS would be enough for any subsequent procedures and at least would not be a limiting factor in successful honeybee genome editing. Recently, Roth et al (2019) have shown one-step honeybee genome editing protocol which allows phenotype observation without subsequent screening and mating (Roth et al 2019). However, there are many phenotypes that can only be measured from substantial numbers of mutants such as social behaviors and resistance to stress factors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, with both traditional and newly developed genetic approaches, researchers have begun to experimentally manipulate candidate genes to confirm their effects on social behavior [14,16]. Because the genetic bases of social behavior are apparently very complex, these experimental studies, which are typically limited to one or a few genes that are a priori of interest, will need to be coupled with the unbiased approaches described above in order to gain a full understanding of the genetic basis and evolution of social behavior.…”
Section: Progress Toward Characterizing the Genetic Basis Of Social Imentioning
confidence: 99%